O direito de arrependimento nos contratos eletrônicos - Brandão, Caio Rogério da Costa (2016)
Submitted by Renata Ribeiro (rribeiro@stj.jus.br) on 2016-09-16T19:10:04Z No. of bitstreams: 2 direito_arrependimentos_contratos_brandao.pdf: 1117592 bytes, checksum: 52a26f65e3ce5cc8627b825a843dfd27 (MD5) license.txt: 1239 bytes, checksum: c9b4c351324448672315a00808efb725 (MD5)